Lipid Acyl Chain Remodeling in Yeast - Renne, Mike F. (Lipid Insights, 2016)
Membrane lipid homeostasis is maintained by de novo synthesis, intracellular transport, remodeling, and degradation of lipid molecules. Glycerophospholipids, the most abundant structural component of eukaryotic membranes, are subject to acyl chain remodeling, which is defined as the post-synthetic process in which one or both acyl chains are exchanged. Here, we review studies addressing acyl chain remodeling of membrane glycerophospholipids in Saccharomyces cerevisiae, a model organism that has been successfully used to investigate lipid synthesis and its regulation. Experimental evidence for the occurrence of phospholipid acyl chain exchange in cardiolipin, phosphatidylcholine, phosphatidylinositol, and phosphatidylethanolamine is summarized, including methods and tools that have been used for detecting remodeling. Progress in the identification of the enzymes involved is reported, and putative functions of acyl chain remodeling in yeast are discussed.